Revolusi! Indonesia independent - Stevens, Harm 1969-; Sidharta, Amir 19XX-; Triyana, Bonnie 1979-; Anker, Marion 19XX- (Rijksmuseum, 2022)
A book and an exhibition on the impassioned pursuit of a free Indonesia after a long period of colonial domination. It looks at how people fought, how they negotiated, and how the revolution defined lives.0We will reflect a history with many faces and many voices, by zooming in on the personal stories of individuals who lived through these events from 1945 to 1949.0The team of Indonesian and Dutch curators will bring together stories, historical objects, artworks, propaganda posters, films and photographs that testify to a turbulent past.
Keywords: Indonesischer Unabhängigkeitskrieg; Ausstellungskatalog -- Rijksmuseum Amsterdam -- 11.02,2022-06.06.2022 -- Amsterdam